Experimental and Numerical Simulation for Bulk Nanostructure of AL-6082 Alloy Material Produced by Equal-Channel Angular Pressing (ECAP) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Equal-channel angular pressing (ECAP) is asevere plastic deformation (SPD) method, which used toproduce ultra fine-grained (UFG) material . Theconventional way to develop press-formed metalliccomponents requires a burden some trial-and-error processfor setting-up the technology, whose success depends largelyon the operator’s skill and experience [6,7]. The finiteelement (FE) simulations of ECAP process help themanufacturing engineer to design a forming process byshifting the costly press-shop try-outs to the computer-aideddesign environment. Numerical simulations of amanufacturing process, such as ECAP, have beenintroduced, in order to avoid the trial-and-error procedureand to shorten the development phases when tight time-tomarketis demanded. The main aim of the investigationpresented in this paper is to develop a numerical model thatwould be able to successfully simulate the ECAP pressing.The finite-element method was used for die and billetbehaviorpredictions during the process. The as-receivedalloy used in this study was the 6082 commercial Al-Mg-Sialloy. High strength and high ductility phenomenon whichrecently was found in materials after ECAP were reachedwith the route C technique up to eight passes with a highlength to diameter ratio i.e. 15-16. The induced anisotropyof specimens after ECAP was monitored.